2008
DOI: 10.1093/jb/mvn123
|View full text |Cite
|
Sign up to set email alerts
|

The Scaffold Protein c-Jun NH2-Terminal Kinase-associated Leucine Zipper Protein Regulates Cell Migration through Interaction with the G Protein G 13

Abstract: Scaffold proteins for MAP kinase (MAPK) signalling modules play an important role in the specific and efficient signal transduction of the relevant MAPK cascades. Here, we investigated the function of the scaffolding protein c-Jun NH 2 -terminal kinase (JNK)-associated leucine zipper protein (JLP) by depleting it in cultured cells using a short hairpin RNA (shRNA) against human JLP. HeLa and DLD-1 cells stably expressing the shRNA showed a defect in cell migration. The re-expression of fulllength shRNA-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Using a panel of pancreatic cancer cells, consisting of BxPC3, Dan-G, Panc-1, MDAPanc-28, and MIA-PaCa-2 (PaCa-2) cell lines, we demonstrate here that LPA specifically stimulates the migration of pancreatic cancer cell lines but not their proliferation. Our results also establish that the invasive migration of pancreatic cancer cells stimulated by LPA is inhibited by the expression of a competitively inhibitory minigene of Gα 13 that encodes the C-terminal eleven amino acids of Gα 13 , which is known to disrupt receptor-Gα 13 interaction 25-27 . Similar inhibition of LPA-stimulated migration of pancreatic cancer cells is also demonstrated by shRNA-mediated silencing of Gα 13 in these cells.…”
Section: Introductionsupporting
confidence: 69%
“…Using a panel of pancreatic cancer cells, consisting of BxPC3, Dan-G, Panc-1, MDAPanc-28, and MIA-PaCa-2 (PaCa-2) cell lines, we demonstrate here that LPA specifically stimulates the migration of pancreatic cancer cell lines but not their proliferation. Our results also establish that the invasive migration of pancreatic cancer cells stimulated by LPA is inhibited by the expression of a competitively inhibitory minigene of Gα 13 that encodes the C-terminal eleven amino acids of Gα 13 , which is known to disrupt receptor-Gα 13 interaction 25-27 . Similar inhibition of LPA-stimulated migration of pancreatic cancer cells is also demonstrated by shRNA-mediated silencing of Gα 13 in these cells.…”
Section: Introductionsupporting
confidence: 69%
“…It appears that JLP modulates JNK-dependent phosphorylation of SCG10 and thereby NGF-induced neurite extension by sequestering JNK and/or SCG10 into a non-productive signaling complex. In fact, recent studies have shown that JLP can modulate physiological responses by sequestering active signaling components in different subcellular regions (20).…”
Section: Discussionmentioning
confidence: 99%
“…One such well studied scaffolding protein family is the family of JNK-interacting proteins (JIPs). 5 The JIP family consists of four members: JIP1, JIP2, JIP3, and JLP (2). Of all the members characterized in the JIP family, JLP is characterized by the presence of two leucine zipper domains and a JNK binding domain in its N terminus and a conserved C-terminal domain, all of which functions in binding to and forming specific cell signaling complexes (3).…”
mentioning
confidence: 99%
“…Of all the members characterized in the JIP family, JLP is characterized by the presence of two leucine zipper domains and a JNK binding domain in its N terminus and a conserved C-terminal domain, all of which functions in binding to and forming specific cell signaling complexes (3). Although JLP is ubiquitously expressed, previous studies have shown that the protein plays a role in regulating neurite outgrowth by interacting with SCG10 (4), activating JNK/p38 MAPK signaling (3), regulating cell migration by interacting with G␣12 and G␣13 (5,6), and functioning in vesicle transport by binding to kinesin light chain (KLC1) and dynein microtubule motor proteins (7). Recent studies have identified that JLP and JIP3 can interact with ADP-ribosylation factor 6 (ARF6), a small G protein that function in the regulating cytokinesis by transporting recycling endosomes to the cleavage furrow (8).…”
mentioning
confidence: 99%